Il divenire della disciplina urbanistica: il contributo di Carlo Monti: The becoming of spatial planning: the contribution of Carlo Monti - Monti, Carlo (TeMA - Journal of Land Use, Mobility and Environment, 2023)
With this volume - Conversations with TeMA - the Journal opens a new editorial line specifically dedicated to promoting and disseminating the discussion between worldwide researchers on specific issues concerning the contents, methods and timing of our work. This first experience is dedicated to a deepening, in an interview formula, on the future of spatial planning in Italy both from a regulatory and technical-disciplinary perspective, also concerning what is happening in other countries. In line with the aims we had set, we decided to involve, in this first phase, both colleagues working in Italian universities and those working in foreign universities and research centres. This contribution is by Carlo Monti, Former Full Professor in Urban Planning, Alma Mater Studiorum University of Bologna